The real Tales of Hoffmann origin, history, and restoration of an operatic masterpiece - Kaye, Michael 1948-; Giroud, Vincent 1953- (Rowman & Littlefield, 2017)
Of all operas in the standard repertory, none has had a more complicated genesis and textual history than Offenbach’s "Tales of Hoffmann". Based on a highly successful 1851 play inspired by the short stories by the German Romantic writer E.T.A. Hoffmann, the work occupied the last decade of Offenbach's life. When he died in October 1880, the work was being rehearsed at the Opéra-Comique. At once cut and rearranged, the work was performed from the start in versions that ignored the composer's final intentions. Only a few decades ago, when previously unavailable manuscripts came to light, it became possible to reconstitute the score in its real form. Vincent Giroud and Michael Kaye’s "The Real Tales of Hoffmann" tells the full story for the first time in English. After discussing how the work of Hoffmann became known and influential in France, the book includes little-known sources for the opera, especially the complete Barbier and Carré play, in French and English. It describes the genesis of the opera. The annotated libretto is published in full, with the variants, for the two versions of the opera: with spoken dialogue or recitatives. Essays explain what was done to the opera after Offenbach's death, from the 1881 Opéra-Comique production to more recent restoration attempts. There is also a survey of "Les contes d’Hoffmann" in performance from the 1970s to the present, and supplementary information, including discography, filmography, and videography.